Precise homogenization rates for the Fučík spectrum - Salort, Ariel Martin (2017)
Given a bounded domain Ω in RN, N≥ 1 we study the homogenization of the weighted Fučík spectrum with Dirichlet boundary conditions. In the case of periodic weight functions, precise asymptotic rates of the curves are obtained.